The biomechanics of maintaining effective force application across cycling positions. (June 2022) - Jongerius, N.; Wainwright, B.; Walker, J.; Bissas, A.
Abstract: Cyclists are known to change their cycling position to reduce aerodynamic drag. Research has shown that this compromises their physical capacity to perform, but there is considerable inter-individual variability present. Proposed training specificity effects by cycling position do not explain all of the observations in the literature, so a search for other influencing parameters is warranted and might help practitioners to further optimise cycling position. This study captured full-body kinematics and 2D crank forces in 19 Time-Trial (TT) and 36 Road trained cyclists. Data in preferred and standardised cycling positions were systematically evaluated and showed that, amongst other kinematic differences, TT cyclists prefer a more forwardly positioned hip joint over Road cyclists. Despite their different setup, no effects in mechanical effectiveness were seen between the groups when tested in their preferred position. Across the standardised positions, the full cohort showed lower mechanical effectiveness when lowering trunk angle. However, significant group by position interactions showed this effect to be less extreme for the TT group. Kinematic data revealed that an increased pelvic tilt resulted in increased hip flexion and induced a more dorsiflexed ankle angle. In addition, linear hip position acutely responded to positional changes by moving forwards when the trunk angle was lowered. A more forwards hip position is thus associated with maintaining a better mechanical effectiveness in aerodynamic cycling positions. This suggests that there is potential to mitigate the effect of negative crank forces in aerodynamic positions by acutely adjusting the saddle placement to facilitate linear hip movement.